The microtheory of innovative entrepreneurship - Baumol, William J. (Kauffman Foundation series on innovation and entrepreneurship., 2010)
Entrepreneurs are widely recognized for the vital contributions they make to economic growth and general welfare, yet until fairly recently entrepreneurship was not considered worthy of serious economic study. Today, progress has been made to integrate entrepreneurship into macroeconomics, but until now the entrepreneur has been almost completely excluded from microeconomics and standard theoretical models of the firm. The Microtheory of Innovative Entrepreneurship provides the framework for introducing entrepreneurship into mainstream microtheory and incorporating the activities of entreprene.